2015
DOI: 10.1007/s12079-015-0268-8
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK and PI3K pathways mediate CNTF-induced neuronal survival and process outgrowth in hypothalamic organotypic cultures

Abstract: While collateral sprouting has been shown to occur in a variety of neuronal populations, the factor or factors responsible for mediating the sprouting response remain largely un-defined. There is evidence indicating that ciliary neurotrophic factor (CNTF) may play an important role in promoting neuronal survival and process outgrowth in neuronal phenotypes tested to date. We previously demonstrated that the astrocytic Jak-STAT pathway is necessary to mediate CNTF-induced oxytocinergic (OT) neuronal survival; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 101 publications
(149 reference statements)
0
27
0
2
Order By: Relevance
“…4) [46][47][48]. CNTF induced PI3K/Akt pathway was shown to be important in survival and neurite growth of neuroblastoma cells and responsible for CNTF effect on skeletal muscle glucose uptake [49][50][51]. MAPK-ERK1/2 pathway was demonstrated to play an important role in CNTF induced neuronal survival in stationary hypothalamic cultures [50].…”
Section: Cntf Receptors and Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…4) [46][47][48]. CNTF induced PI3K/Akt pathway was shown to be important in survival and neurite growth of neuroblastoma cells and responsible for CNTF effect on skeletal muscle glucose uptake [49][50][51]. MAPK-ERK1/2 pathway was demonstrated to play an important role in CNTF induced neuronal survival in stationary hypothalamic cultures [50].…”
Section: Cntf Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…CNTF induced PI3K/Akt pathway was shown to be important in survival and neurite growth of neuroblastoma cells and responsible for CNTF effect on skeletal muscle glucose uptake [49][50][51]. MAPK-ERK1/2 pathway was demonstrated to play an important role in CNTF induced neuronal survival in stationary hypothalamic cultures [50]. Whereas STAT3 phosphorylation can be regulated by mTOR, CNTF activation of MAPK-ERK1/2 appears to be mediated through JAK2-dependent Ras and Raf activation [52].…”
Section: Cntf Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…In brief, following dissociation, the cortical tissue was plated on 75-cm 2 poly-d-lysine-coated culture flasks in Dulbecco's modified Eagle's medium (DMEM)/F12 (1:1) supplemented with 100 µg/ml streptomycin, 100 U/ml penicillin and 10% fetal bovine serum (Gibco, Thermo Fisher Scientific, Inc., Waltham, MA, USA). The cultures were maintained in a humid incubator at 37˚C in 5% CO 2 . After confluence at 7-10 days in vitro (DIV), the cells were agitated at 37˚C at 250 rpm for Immunoassay.…”
Section: Methodsmentioning
confidence: 99%
“…Ciliary neurotrophic factor (CNTF), a survival factor for chick ciliary neurons (1), is reported to facilitate the survival of several types of neurons such as sympathetic, sensory and motor neurons (2). In addition, it has important roles in triggering neurite outgrowth, preventing neuronal degeneration and attenuating motor deficits (3).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several reports have shown that ROS are involved in triggering apoptosis signaling in cancer cells including prolonged MAPK activation and inhibition of p-STAT3 and NF-κB(Askvig & Watt, 2015;Zuo et al, 2016). 4a).…”
mentioning
confidence: 99%